Assessing cocaine abuse using LC–MS/MS measurements in biological specimens. (July 2015) - Barroso, Mário; Gallardo, Eugenia
Cocaine use is still a problem in today's world, and this has several implications on human activities. Indeed, important problems related to cocaine derive from its use in situations where concentration and focus skills are necessary, namely while driving and/or working. The need of analytical methods for drug analysis in specimens of biological origin for proper documentation of human exposure is increasing. While GC–MS-based procedures represented the state-of-the-art of analytical techniques a few years ago, there is a growing trend for their replacement by LC–MS/MS, which can be justified by the increased sensitivity presented by these new technologies. This paper will review recently published papers on the use of LC–MS/MS-based procedures for cocaine measurement in biological specimens.